PARAMETER KEBENARAN ILMU PENGETAHUAN (SAINS) DALAM AL-QUR'AN - Almannah Wassalwa (LP2M Universitas Ibrahimy, 2015)
The truth of science can really know rightfully. Truth is the culmination epistemology that leads to metaphysics. The essence of science is a fitting information, object, theory with reality. In metaphysical aspect and the absolute transcendental reality, the truth’s parameter is the text of wahyu (Qur'an and Hadits) whose the meaning is unknown by ijma’ and logic. The truth of science can be proven in the Qur'an, are contained within a wide range of knowledge that absolute truth and authenticity that can’t be uncertainted, and it Al-Qur’an has special status to among the others